Antimicrobial activity of Glechon spathulata BENTH crude extract and fractions (Research, Society and Development, 2021)
The medicinal species Glechon spathulata Benth, belonging to the family Lamiaceae, known as the "Mangeroninha-do-campo". The objective of the study was to evaluate the antimicrobial activity of the crude extract and fractions obtained in open - column chromatography of G. spathulata through the broth microdilution method, to test against different gram positive and gram-negative bacteria. According to the results obtained, the greatest inhibitory potential occurred against gram negative bacteria. The fractions C and E, G fraction and crude extract presented better results against gram negative bacteria, and the highest inhibitory potential occurred in relation to the two strains of Escherichia coli (ATCC 35218 and ATCC 25922). The crude extract and C and F fractions showed a greater inhibitory effect against Salmonella tiphymurium ATCC 52117. There was also an inhibitory potential against Staphylococcus aureus strains ATCC 25923, both for the crude extract, as well as fractions C and B And fractions F and G. Inhibition of Staphylococcus epidermidis strains ATCC 12228 occurred only in crude extract and ethyl acetate fractions. Both the crude extract and the fractions of G. spathulata presented a potential antibacterial activity. The extract and the fractions presented better activity against the strain of Salmonella tiphymurium when compared to studies that used the same plant and plants of the same family. This study showed that both the crude extract and some fractions of Glechon spathulata Benth are potential candidates for the development of new antimicrobial agents.